Powered Lower-Limb Exoskeletons to Restore Gait for Individuals with Paraplegia – a Review - Chang, Sarah R. (Case Orthop J, 2015)
Individuals with paraplegia due to spinal cord injury rank restoration of walking high on the list of priorities to improving their quality of life. Powered lower-limb exoskeleton technology provides the ability to restore standing up, sitting down, and walking movements for individuals with paraplegia. The robotic exoskeletons generally have electrical motors located at the hip and knee joint centers, which move the wearers' lower limbs through the appropriate range of motion for gait according to control systems using either trajectory control or impedance control. Users of exoskeletons are able to walk at average gait speeds of 0.26 m/s and distances ranging between 121-171 m. However, the achieved gait speeds and distances fall short of those required for full community ambulation (0.8 m/s and at least 230 m), restricting use of the devices to limited community use with stand-by assist or supervised rehabilitation settings. Improvement in the gait speed and distance may be achievable by combining a specially designed powered exoskeleton with neuromuscular stimulation technologies resulting in a hybrid system that fully engages the user and achieves the necessary requirements to ambulate in the community environment with benefits of muscle contraction.